The Fruits of Siraitia grosvenorii: A Review of a Chinese Food-Medicine - Gong, Xue; Chen, Namuhan; Ren, Kai; Jia, Junying; Wei, Kunhua; Zhang, Le; Lv, Ying; Wang, Jianhua; Li, Minhui (Frontiers in Pharmacology, 2019)
Siraitia grosvenorii (Swingle) C. Jeffrey, a member of the family Cucurbitaceae, is a unique economic and medicinal plant grown in China. For more than 300 years, S. grosvenorii has been used as a natural sweetener and as a traditional medicine for the treatment of pharyngitis, pharyngeal pain, as well as an anti-tussive remedy in China. It is one of the first approved medicine food homology species in China. It has been widely studied as a natural product with high development potential. Therefore, the present paper provides a review of the botanical characterization, traditional uses and ethnopharmacology, food and nutritional values, chemical constituents, pharmacological effects, toxicology, and development direction for the future of S. grosvenorii. Phytochemical studies have revealed that the chemical composition of this plant mainly includes iridoid and phenylpropanoid glycosides. Several compounds such as triterpenoids, flavonoids, and amino acids have been isolated from the plant. S. grosvenorii and its active constituents possess broad pharmacological properties, such as antioxidant, hypoglycemic, immunologic, anti-tussive and sputum-reducing, hepatoprotective, and antimicrobial activities, etc. By documenting the comprehensive information of S. grosvenorii, we hope to establishes the groundwork for further research on the mechanism of action of S. grosvenorii and its development as a new health food in the future.